The Effect of Price and Design of Honda Beat Motorcycle Products on Purchase Decisions at Honda Dealers PT. PAS Sudirman, Bengkulu City - Ditantio Pramana; Oni Yulianti; Zahra Indah Ferina (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the effect of price (X1), product design (X2) Honda Beat motorcycles on purchasing decisions (Y) at Honda Dealer PT. PAS Sudirman Bengkulu City. This type of research is descriptive quantitative research, using Random Sampling technique. The data analysis techniques used are Normalization Test, Validity Test, Multicorlinearity Test, Reliability Test, T Test, F test, Multiple Linear Regression, Multiple Correlation Analysis (R), Determination Analysis (R2), using the SPSS program for windows 23.00 . The number of samples is 75 respondents. The results show that it is known from the multiple linear regression equation, Y = 29.391 + 0.083 (X1) + 0.396 (X2) where Y is the purchase decision, the beta coefficient (B) is 29.391, which means that if there are no price and product design variables, the decision purchases amounted to 29,391. The regression coefficient for the price variable (X1) is 0.083, meaning that if the product design has a fixed value and the price increases by 1, the purchase decision will increase by 0.083. The coefficient is positive, meaning that there is a positive relationship between price and purchase decisions, the higher the store price, the higher the purchase decision. The value of the product design coefficient (X2) is 0.396, which means that if the other independent variable (price) remains constant and the product design increases by 1%, the purchase decision (Y) will increase by 0.396. The positive coefficient means that there is a positive relationship between product design and purchase decisions, the better the product design, the greater the chances of consumers in deciding to buy/shop..